Determinasi Ketimpangan Pendapatan Antar Propinsi di Indonesia : Analisis Panel dengan Pendekatan Fixed Effect Model (2019-2023) - Asykurunnizza, Anindya Zulfa; Adistia, Rintan Della; Oktavia, Sinta; Febriani, Reva Ghani; Hadi, Muhammad Abdul; Diniati, Bintis Ti’anatud (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2025)
Income inequality is one of the main development challenges in Indonesia. Income distribution remains uneven despite the country's growing economy. In addition, inequality between provinces such as between Papua and DKI Jakarta is clearly visible. This study aims to evaluate various factors including economic growth, per capita expenditure, Life Expectancy (UHH), Average Years of Schooling (RLS), poverty, Foreign Direct Investment (FDI), and income inequality. Quantitative methods were used with panel data from ten provinces during 2019-2023. The Fixed Effect Model (FEM) approach was used in the panel data analysis process through panel regression. Then Chow, Hausman, and Lagrange Multiplier (LM) tests were conducted. This study shows that economic growth, per capita expenditure, UHH, and poverty have a large effect on income inequality. RLS and FDI do not have a significant impact. The discussion shows that improvements in quality of life and economic welfare tend to reduce inequality, but education and investment allocation are uneven. It is evident that poverty is not only an effect but also a cause of inequality.